2016
DOI: 10.1161/jaha.115.003118
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Mitochondrial Cardiolipin Attenuates Cardiac Damage in Swine Renovascular Hypertension

Abstract: BackgroundRenovascular hypertension (RVH) impairs cardiac structure and left ventricular (LV) function, but whether mitochondrial injury is implicated in RVH‐induced myocardial damage and dysfunction has not been defined. We hypothesized that cardiac remodeling in swine RVH is partly attributable to cardiac mitochondrial injury.Methods and ResultsAfter 12 weeks of hypercholesterolemic (HC)‐RVH or control (n=14 each), pigs were treated for another 4 weeks with vehicle or with the mitochondrial‐targeted peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 77 publications
(133 reference statements)
2
59
0
Order By: Relevance
“…In agreement, we have found that both cardiac and renal cardiolipin content is reduced in pigs with renovascular hypertension [11, 12]. Importantly, oxidation and consequent loss of cardiolipin destabilizes the ETC, triggering local generation of ROS and mitochondrial dysfunction [22].…”
Section: Mechanisms Of Mitoprotectionmentioning
confidence: 56%
See 1 more Smart Citation
“…In agreement, we have found that both cardiac and renal cardiolipin content is reduced in pigs with renovascular hypertension [11, 12]. Importantly, oxidation and consequent loss of cardiolipin destabilizes the ETC, triggering local generation of ROS and mitochondrial dysfunction [22].…”
Section: Mechanisms Of Mitoprotectionmentioning
confidence: 56%
“…Preservation of mitochondrial cardiolipin attenuated swine stenotic-kidney microvascular loss and injury, and improved renal oxygenation, hemodynamics, and function [12]. ELAM also blunted myocardial hypertrophy, improved left ventricular relaxation, and attenuated myocardial cellular and microvascular remodeling in these pigs [11]. Intravenous administration of ELAM in conjunction with renal revasculatization also improved cardiac and renal outcomes in pigs with renovascular hypertension [10, 13].…”
Section: Mechanisms Of Mitoprotectionmentioning
confidence: 99%
“…This protein is highly vulnerable to oxidative damage and subsequent loss, therefore leading to mitochondrial loss and contributing to development of cardiovascular disorders. The authors also demonstrate that restoration of cardiolipin improves cardiac function of pigs subjected to renovascular hypertension [43]. Therefore, all these observations indicate that the response of altering proton conductance depends on the etiology of hypertension.…”
Section: “Uncoupling” In Pathogenesis Of Cardiovascular Diseasementioning
confidence: 92%
“…Renal expression of cardiolipin synthase (CRLS)-1 was measured by western blot (26), and mRNA expression of the cardiolipin remodeling enzyme taffazin (Taz)-1 (27) by real-time quantitative polymerase chain reaction (28). …”
Section: Methodsmentioning
confidence: 99%